Association of Weight and Body Composition on Cardiac Structure and Function in the ARIC Study (Atherosclerosis Risk in Communities). (August 2016) - Bello, Natalie A.; Cheng, Susan; Claggett, Brian; Shah, Amil M.; Ndumele, Chiadi E.; Roca, Gabriela Querejeta; Santos, Angela B.S.; Gupta, Deepak; Vardeny, Orly; Aguilar, David; Folsom, Aaron R.; Butler, Kenneth R.; et al.
Abstract : Background—: Obesity increases cardiovascular risk. However, the extent to which various measures of body composition are associated with abnormalities in cardiac structure and function, independent of comorbidities commonly affecting obese individuals, is not clear. This study sought to examine the relationship between body mass index, waist circumference, and percent body fat with conventional and advanced measures of cardiac structure and function. Methods and Results—: We studied 4343 participants of the ARIC study (Atherosclerosis Risk in Communities) who were aged 69 to 82 years, free of coronary heart disease and heart failure, and underwent comprehensive echocardiography. Increasing body mass index, waist circumference, and body fat were associated with greater left ventricular (LV) mass and left atrial volume indexed to height 2.7 in both men and women ( P <0.001). In women, all 3 measures were associated with abnormal LV geometry, and increasing waist circumference and body fat were associated with worse global longitudinal strain, a measure of LV systolic function. In both sexes, increasing body mass index was associated with greater right ventricular end-diastolic area and worse right ventricular fractional area change ( P ⩽0.001). We observed similar associations for both waist circumference and percent body fat. Conclusions—: In a large, biracial cohort of older adults free of clinically overt coronary heart disease or heart failure, obesity was associated with subclinical abnormalities in cardiac structure in both men and women and with adverse LV remodeling and impaired LV systolic function in women. These data highlight the association of obesity and subclinical abnormalities of cardiac structure and function, particularly in women. Abstract : Supplemental Digital Content is available in the text.